Design of a Temperature and Humidity Monitoring System in Broiler Farms Using Internet of Things-Based Thingspeak - Aji Susanto; Abdur Rohman Ardi Agung; Mohammad Ibrahim; Toto Dwi Sugiarto; Andrie Yuswanto; Budi Wibowo (Sultan Publisher, 2023)
Broiler chickens or also called broiler chickens are a type of chicken specifically designed for meat production in a relatively short time. They have fast growth and have high meat quality. Optimal temperature is very influential to achieve high productivity of broiler chickens. Broiler chicken coops require proper temperature regulation to create an optimal environment for the growth and health of the chickens. In this study, I propose the use of automatic light activation as a method for efficiently controlling broiler coop temperature. The method used involves installing a temperature sensor in the cage connected to a control system. When the temperature inside the cage exceeds or falls below a set limit, the control system will automatically turn on or off the light to maintain the desired temperature. The temperature settings tested in this study included the minimum and maximum temperatures set to achieve thermal comfort for broiler chickens. In addition, I also observed the effect of the duration of the light on the temperature in the cage.